The Antibacterial And Anti-Adhesion Effects Of Date Fruit Extracts (Phoenix Dactylifera) Against Bacteria Causing Gastroenteritis - Nurul Farhana Binti Mohd Ishak
Acute gastroenteritis was reported to lead to five billion cases worldwide and nearly 1.5 million deaths per year. Although this condition is predominantly caused by viral infections, bacterial gastroenteritis is more severe, while some conditions might require antibiotic treatment. In recent years, there has been an increasing interest among consumers’ regarding prophetic food, such as black seed, dates, goat milk, honey, and figs as alternative treatments. Although previous studies recorded the antioxidant, anti-mutagenic, anti-inflammatory, and antimicrobial activities, there was no research focusing on the bacteria gastroenteritis. This study aims to investigate the antibacterial effects of date fruit (Phoenix dactylifera) extract and the mechanisms involved against clinically important bacterial gastroenteritis. In-vitro studies were conducted using the extract of three different types of dates, including Ajwa, Medjool, and Mariami. The dates were extracted using cold aqueous, hot aqueous, and methanol, followed by the testing of antibacterial activities using well diffusion assay method against Staphylococcus aureus, Salmonella enterica serotype Typhi, Salmonella enterica serovar Typhimurium, Shigella flexneri, Escherichia coli, and Vibrio cholerae. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extract of the date were also determined, followed by the examination of anti-adhesion activity using Caco-2 cells model. Active compounds i.e. flavonoid and phenolic were isolated from the dates and tested for their antibacterial effect. The antibacterial mechanism of date extracts and active isolated fractions was later determined using electron microscopy. As a result, all three types of dates showed good antibacterial activity, while the methanol extract of Ajwa dates exhibited the strongest antibacterial effect with the inhibition zone of 25 - 27.33 mm against S. Typhi, V. cholerae, and E. coli (p<0.05). The dates also showed good anti-adhesion activity up to 95.6% against all tested bacteria, with hot aqueous extract of Ajwa dates showing the highest anti-adhesion activity compared to Medjool and Mariami dates. Phytochemical analysis indicated that the Ajwa dates contained significantly higher phenolic and flavonoid content compared to Medjool and Mariami dates (p<0.05), while isolated flavonoids (e.g.; luteolin, catechin, lutein, kaempferol, and cyanidin) in Ajwa dates showed antibacterial activity against S. Typhimurium, S. flexneri, and V. cholerae with the inhibition zone ranging from 13 – 26 mm and MIC values ranging from 3.125 mg/ml to 6.25 mg/ml. The MBC value of flavonoids could only be determined for V. cholerae with an MBC value of 3.125 mg/ml. Moreover, the isolated flavonoids showed 47% of anti-adhesion activity. It was found from the electron microscopy that both date extract and isolated flavonoids could cause ultra-structural damages to the bacterial cell wall, blisters on the cells , shrunken of the cells, and lysis of the cells. Luteolin, catechin, lutein, kaempferol, and cyanidin in Ajwa dates extract had a role in their antibacterial activity and they could cause ultra-structural damage to the bacterial cell wall, which results in cell death. This study showed that date fruits exhibited antibacterial properties which able to kill bacteria and prevent bacterial adhesion that can leads to gastroenteritis. The finding of this study suggests that the Ajwa date fruits can be used as a functional food or complementary alternative treatment to prevent/treat bacterial gastroenteritis.